Understanding Sarinah as an Arena for Feminism Education Based on Local Culture: Memahami Sarinah Arena Pendidikan Feminisme Berbasis Budaya Lokal - Nyoman Suwarta; Dwi Astutiek; Edi Dwi Riyanto; Ahmad Nurefendi Pradana; Bambang Kusbandrijo; Yopi Lutfi Subargo (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: Feminism education is crucial for fostering mutual respect and understanding of gender differences, emphasizing the social identity of archipelago feminism. This approach embraces the values of womanhood rooted in Indonesian culture and customs. Specific Background: The book